Analisis Gerak Pointing Pada Olahraga Petanque - Bustomi, Adhe Oktaria; Hidayah, Taufiq; Okilanda, Ardo; Putra, Dede Dwiansyah (Journal Sport Area, 2020)
This study aimed to analyze pointing movement skill of Semarang Petanque athlete. This study was descriptive quantitative design which described systematically facts and characteristics of pointing movement by Semarang Petaque Athlete. The pointing movements as data were descriptive. This analysis used descriptive statistic which measured frequency. This data was taken from Biomechanics aspect of 3 pointing movements of Petaque by 8 men and women players of Semarang city. They were; (1) holding a boule, (2) foot position, and (3) throwing the boule. The measurement was carried out by two national coaches and one international coach of Petaque. The result shows that; 1) the average value of holding a boule is 4.4 or 88% of percentage which categorized as very good, 2) the average value of foot position is 4.6 or 92% of percentage which categorized as very good, and 3) the average value of throwing a boule is 3.72 or 74.4% of percentage which categorized as good. Overall movements point out good category with 88% of percentage.